2020
DOI: 10.13189/ujer.2020.080438
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Factors that Influence the Use of Digital Technologies in Teaching: A Case Study

Abstract: In the last decade we have a great development of Informat ion and Commun ication Technologies (ICTs). As a result, educational institutions are increasingly incorporating these digital technologies into the teaching and learning process. Governments are making major investments to increase ICTs infrastructure in educational institutions and to train teachers to use these technologies in the teaching process. In this paper the main objectives of this study were to analy ze ICTs availab ility and use by student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
1
0
0
Order By: Relevance
“…The intimacy which refers to the teacher's depth in mastering digital technology, will certainly strengthen the teacher's confidence and trust in his teaching ability. This is also evidenced by previous relevant research which revealed that the intimacy of digital technology plays a very important role in online learning that requires a comprehensive integration of digital technology [57]- [59].…”
Section: Discussionsupporting
confidence: 55%
“…The intimacy which refers to the teacher's depth in mastering digital technology, will certainly strengthen the teacher's confidence and trust in his teaching ability. This is also evidenced by previous relevant research which revealed that the intimacy of digital technology plays a very important role in online learning that requires a comprehensive integration of digital technology [57]- [59].…”
Section: Discussionsupporting
confidence: 55%
“…The study suggests that ICT can be used in science education to provide access to internet resources, make learning active and constructive, and increase the interest and motivation of learners and their involvement in classroom activities. A study by Prodani, Çobani, Bushati and Andersons (2020) explored the ICTs availability and use by students and by their teachers in the Korca region of Albania. The study found that while some teachers used ICT tools such as multimedia presentations and online resources, many faced challenges related to limited access to technology and a lack of digital training.…”
Section: Introductionmentioning
confidence: 99%
“…Developing nations are integrating digital technology into their educational systems to improve academic performance (Barbosa Neves et al, 2019;Kholifah et al, 2022). The utilisation of digital technology by educators to teach subject-specific knowledge to pupils has a notable influence (O'Donovan & Smith, 2020;Prodani et al, 2020). Instructional methods need to adapt to include digital learning technology (König et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It implies that infrastructure conditions necessitate that educators master and implement digital technology in accordance with their field. In contrast, studies suggest that the increasing reliance on digital technology in modern times necessitates a more significant investment in infrastructure (Prodani et al, 2020). Vocational instructors are permitted to implement digital technology innovatively so long as the necessary conditions are fulfilled (Nurtanto et al, 2022).…”
Section: Introductionmentioning
confidence: 99%